Iris tectorum Japanese Roof Iris, Wall Iris - Edward Gilman; David Marshall (EDIS)
This document provides an overview of the Japanese roof iris (Iris tectorum), detailing its characteristics, growth habits, and uses. The plant features light-green, coarse-textured foliage and blue flowers that bloom in the spring. It thrives in USDA hardiness zones 6 through 10 and can be planted year-round in zones 7 to 10. The Japanese roof iris is suitable for use as a border, ground cover, or mass planting, and it is known for its high drought tolerance and moderate growth rate. The document also highlights the plant’s preference for well-drained, partially shaded locations and its minimal pest issues. Original publication date October 1999.